2004
DOI: 10.1038/sj.eye.6701771
|View full text |Cite
|
Sign up to set email alerts
|

Iatrogenic eccentric full thickness macular holes following vitrectomy with ILM peeling for idiopathic macular holes

Abstract: To our knowledge iatrogenic eccentric full thickness macular holes after macular hole surgery have never been reported. We believe that the location of the holes represents the initial site of ILM elevation. These holes are asymptomatic, have not required any treatment and have not caused any complications in up to 6 years of follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 7 publications
0
50
0
1
Order By: Relevance
“…Only a few cases have been reported [10][11][12]. Several explanations have been suggested for their pathogenesis; however, no consensus has been arrived at.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Only a few cases have been reported [10][11][12]. Several explanations have been suggested for their pathogenesis; however, no consensus has been arrived at.…”
Section: Discussionmentioning
confidence: 93%
“…Karacorlu et al [19] reported chorioretinal lesions, referred to as iatrogenic punctuate chorioretinopathy, caused by end-gripping forceps. Paracentral MHs following ILM peeling in macular hole surgery were first reported by Rubinstein [10]. OCT imaging showed that these holes were located at the limits of the area of ILM peeling (where an outer, unpeeled area had remaining ILM, and an inner area did not), and particularly at the site of the initial ILM elevation induced by micro vitreoretinal (MVR) blade or by the end-gripping forceps, and at the site where we complete ILM peeling.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…135 It is unclear, however, whether this was secondary to the peeling of ILM or other factors such as ICG toxicity and air-infusion stress related to MH surgery. Steven et al, 136 Mason et al, 137 and Rubinstein et al 138 138 also theorized that perhaps a more plausible explanation of hole formation with eccentric location is iatrogenic trauma to the retina while grasping the macular pucker and/or ILM with ILM forceps. Visual field defects have also been described in cases of ILM peeling.…”
Section: Complicationsmentioning
confidence: 96%
“…2 Diplopia with ocular motility disturbances as a result of migrating buckling elements through the recti muscles has been well documented, [3][4][5] including those requiring surgical repositioning of the transected tendon. 3 Ocular motility disturbances did not occur as one might expect in several cases 4-5 that were thought to be unique, in that reattachment of the muscle fibres or sheath relatively closely behind the migrating element possibly allowed preservation of recti function.…”
mentioning
confidence: 99%